Perfil de citocinas inflamatórias em indivíduos submetidos a procedimentos cirúrgicos utilizando propofol ou isoflurano - Mazoti, Marina Ázer [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Introdução. Cirurgia gera no paciente uma resposta inflamatória conhecida como stress. Não está esclarecido o papel dos anestésicos voláteis e venosos na modulação do perfil de citocinas inflamatórias em pacientes saudáveis submetidos a cirurgias eletivas pouco invasivas. Assim, o objetivo deste trabalho foi estudar o perfil das citocinas IL-1 , IL- 6, IL-8, IL-10, IL-12 e TNF- frente à anestesia inalatória com isoflurano e intravenosa com propofol, em pacientes saudáveis submetidos a cirurgias eletivas pouco invasivas. Métodos. Quarenta pacientes ASA I, submetidos à cirurgia de otorrinolaringologia, foram alocados ao acaso para receber anestesia com isoflurano 1 CAM (concentração alveolar mínima) (n = 20) ou com propofol 2 a 4 μg mL-1 (n = 20). Também foram administrados fentanil 5 mg kg-1 e brometo de rocurônio 0,6 mg kg-1 a todos os pacientes. Foram coletados 10 mL de sangue venoso de cada paciente em cada um dos seguintes momentos: antes do início da cirurgia e anestesia (M1), 2 h após o início da cirurgia (M2) e no dia posterior ao ato anestésico-cirúrgico (M3). As concentrações plasmáticas das interleucinas IL-1β, IL-6, IL-8, IL-10 e IL-12 e do fator de necrose tumoral TNF-α foram mensuradas em cada amostra pela técnica de citometria de fluxo, utilizando o método Cytometric Bead Array (CBA). Amostras de sangue venoso de quinze voluntários não submetidos a stress também foram coletadas como controle, dosando nessas amostras as mesmas citocinas. Resultados. A comparação das concentrações plasmáticas de citocinas entre os grupos de anestésicos (M1) e o grupo de voluntários mostrou aumento de IL-8 nos grupos propofol e isoflurano. Os pacientes dos grupos isoflurano e propofol apresentaram baixas concentrações plasmáticas das citocinas pró-inflamatórias IL-1 , IL-12 e TNF- e da anti-inflamatória...

Introduction. A surgery causes in the patient an inflammatory response known as stress. The role of volatile and venous anesthetics on the modulation of inflammatory cytokine profile in healthy patients subjected to minimally invasive elective surgeries is not elucidated. Thus, the aim of this paper was to study the profile of cytokines IL-1 , IL-6, IL-8, IL-10, IL-12 and TNF- under inhalation anesthesia with isoflurane and intravenous anesthesia with propofol in healthy patients subjected to minimally invasive elective surgeries. Methods. Forty ASA-I patients, subjected to otorhinolaryngology surgery, were randomly allocated to receive anesthesia with isoflurane 1 MAC (minimum alveolar concentration) (n = 20) or propofol 2 to 4 μg mL-1 (n = 20). Fentanyl 5 mg kg-1 and rocuronium bromide 0.6 mg kg-1 were also administered to all patients. Venous blood (10 mL) was collected from each patient at each of the following times: before the beginning of surgery and anesthesia (T1), 2 h after the beginning of surgery (T2), and on the day after the anesthetic-surgical procedure (T3). Plasma concentrations of interleukins IL-1β, IL-6, IL-8, IL-10 and IL-12 and tumor necrosis factor (TNF-α) were measured in each sample through flow cytometry technique by using the method Cytometric Bead Array (CBA). Venous blood samples from fifteen volunteers not subjected to stress were also collected as control, and the same cytokines were measured. Results. Plasma concentrations of IL-8 increased in Propofol and Isoflurane groups (T1), compared to the group of volunteers. Patients of Isoflurane and Propofol groups had low plasma concentrations of proinflammatory cytokines IL-1 , IL-12 and TNF- and anti-inflammatory cytokine IL-10 throughout the study period. On the other hand, plasma concentration of IL-6 significantly increased at T2 and T3 in the group of patients... (Complete abstract click electronic access below)
Keywords: Patologia cirurgica; Citocinas inflamatórias; Stress (Fisiologia); Propofol; Volatile anesthetics